An assessment of the relationship between sponsorship and consumer patronage of GSM service providers in Kano metropolis - Adeiza, Adams (Faculty of Entrepreneurship and Business, Universiti Malaysia Kelantan, 2017)
This study attempts to explore the relationship between event sponsorship and consumer patronage of GSM service providers. A survey questionnaire was used to gather data from 395 consumers of GSM services in Kano metropolis, Nigeria. Pearson’s Product-Moment Correlation Coefficient test was conducted. Weighted average was also used to analyze the relative influence of each element of sponsorship on consumer patronage. Contrary to priori expectation, it was found that sponsorship engagements by GSM service providers has no significant relationship with consumer patronage of their services. On the basis of this finding, measures needed to improve return on investment in sponsorship are recommended.